Penyusunan Design Kurikulum Berbasis Kkni Pada Program Studi Tadris Bahasa Inggris PTKIN (Studi Kasus Pada Iain Bengkulu dan STAIN Curup) - Rizkan A. Rahman (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2019)
This study aims to determine the prospects and readiness of two College of Religious Islam Negeri (PTKIN) under the Ministry of Religious Affairs (IAIN Bengkulu and STAIN Curup) which undertake study Program of Tadris English toward discourse of imposition curriculum based KKNI effectively will be enacted in the academic year 2016 / 2017 as which as has been launched nationally through legislation President number 8 in 2012 and later translated into rule of education minester by number 73 in 2013. through the study program or department Tadris English being object of the achievements of learning (learning outcomes) plays as LPTK (educational institution for generating teacher) , namely container nursery candidates qualified English teacher, is worth competitiveness and dedicated. Besides, this research aims to become a means of discovery of solutions to problems that become obstacles from the imposition of KKNI based curriculum. Indonesian National Qualifications Framework (KKNI) is a national reference for improving the quality and competitiveness of Indonesia in the sector of human resources through the achievement of qualifications of human resources Indonesia produced by the educational system and national job training system, as well as learning outcomes assessment system of equality. Improving the quality and competitiveness of the nation will simultaneously strengthen the identity of Indonesia. The results of this study illustrates that both PTKIN which organizes education courses in English in principle ready to perberlakuan KKNI based curriculum in the academic year 2016/2017, but the effectiveness of this policy seyogya coupled with the readiness of all the devices needed especially the structure of matter refers to an element of competence topical; (A) Basis of personality; (B) The mastery of knowledge and skills; (C) Ability to work; (D) Attitudes and behaviors in the work; and (e) Understanding the rules of Bohemian society. PTKIN Of the two, only the TBI study program IAIN Bengkulu who had started implementing the curriculum KKNI and running well while STAIN Curup still in the process of finalizing the structure of the curriculum and the ripening preparation necessary tools.